CHACO BIOME IN BRAZIL: LAND USE, VEGETATION COVER AND SOCIOECONOMICS - Barrozo Chaves, Jô Vinícius; Silva, João dos Santos Vila da; Speranza, Eduardo Antonio (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
The Chaco in Brazil, characterized by wood steppe-savanna vegetation in transition to the Cerrado, exhibits distinct ecological and socio-economic characteristics compared to other Brazilian biomes. However, this fragment is administratively included within the Pantanal, lacking independent legal recognition. To address this gap, public databases and research projects assist in monitoring and analyzing the region, providing support for its management and conservation. Thus, this study aims to analyze land cover change and the socio-economic scenario in the Brazilian Chaco. For this purpose, land use and vegetation cover were examined in the period from 1985 to 2022, while socio-economic data were obtained from the 2017 Agricultural Census. The results indicate a significant replacement of natural vegetation by pasture, totaling approximately 4,832.6 km² of consolidated area, which accounts for 32% of the Brazilian Chaco's territory. The deforested area is primarily associated with livestock farming, the region’s dominant economic activity. An inventory of available tractors was recorded, along with a limited number of agricultural machines, such as seeders and harvesters, highlighting the low intensity of agricultural land use. It is important to highlight that, in addition to the economic significance of livestock farming, the region, particularly the municipality of Porto Murtinho, also exhibits considerable potential for tourism. The availability of spatial databases, pre-classified land cover datasets, and research projects plays a significant role to understand land use and cover dynamics, contributing to develop a public policy for the Brazilian Chaco.